A new species of Oecleus (Hemiptera: Auchenorrhyncha: Fulgoroidea: Cixiidae) from the Caribbean coast of Costa Rica and a reassessment of the generic status of Nymphomyndus - Barrantes, Edwin A. Barrantes; Echavarria, Marco A. Zumbado; Bartlett, Charles R.; Helmick, Ericka E.; Bahder, Brian W. (Zootaxa, 2022)
A new species of cixiid planthopper in the genus Oecleus Stål is described from Tortuguero, Limón Province, Costa Rica. This is the first Oecleus species reported from Costa Rica. The new species, Oecleus dormido sp. n., was collected sweeping grassy edge habitat near the Caribbean coast. Sequence data for COI, 18S, and H3 was generated for phylogenetic comparison of the new species with other available Oecleus species and New World Oecleini to test genus-level placement and provide a preliminary examination of the phylogenetic relationships among New World genera of Oecleini. The results indicate that Oecleus, Haplaxius and Myxia are monophyletic, at least among the included taxa, the genera (Myxia+((Nymphocixia+Nymphomyndus)+Haplaxius) may form a clade apart from Oecleus. The monobasic genera Nymphocixia+Nymphomyndus are closely allied, with a difference of 0.98% for 18S, compared to an average of 2.2% among other included oecleine genera. In view of the limited morphological and molecular differences between these genera, we propose Nymphomyndus as a junior synonym of Nymphocixia.